The global issue of metal contamination in sharks, rays and skates and associated human health risks - Rachel Ann Hauser-Davis; Natascha Wosnick; Ana Paula Chaves; Eloísa Pinheiro Giareta; Renata Daldin Leite; Juan Pablo Torres-Florez (Ecotoxicology and Environmental Safety, 2024)
Elasmobranchs, including sharks, rays, and skates, are a global protein source but face threats from overfishing and population declines. Despite their lower market value, increased consumption raises sustainability and public health concerns. Commonly landed species like the Blue Shark, Shortfin Mako, and Spiny Dogfish are particularly vulnerable to bioaccumulation of metals such as mercury (Hg), lead (Pb), cadmium (Cd), and arsenic (As), posing health risks to consumers. Although metal and metalloid contamination levels in elasmobranchs are frequently reported, studies on specific human health risks remain limited. Sensitive populations, including pregnant women, fetuses, infants, the elderly, and individuals with pre-existing health conditions, face elevated risks from consuming contaminated seafood. Vulnerable communities, especially coastal populations and lower-income groups, encounter further exposure risks due to limited access to safer food alternatives and information. This review explores metal and metalloid contamination in commonly consumed elasmobranch species, associated health risks, and impacts on vulnerable groups, emphasizing the need for informed consumption and the role of contamination awareness in conservation efforts. Arsenic was the most commonly detected element in elasmobranch meat, followed by Se, Hg, Pb, and Cd, with Pb and Se consistently reported at safe levels. Arsenic levels exceeded safety thresholds in most studies, posing health risks, while THQ evaluations indicated significant risks, especially in sharks, where values often surpassed safe thresholds. For C. falciformis, THQ ranged from 5.7 in North America to 38 in Asia, making the consumption of this species inadvisable. Elevated HQ values suggest that cumulative risks likely exceed safe limits, highlighting the need for cautious consumption and further risk assessments.